METADATA - A KEY TO DATA ACQUISITION AND INFORMATION RETRIEVAL - Reusch, Peter J. A. (International Journal of Computing, 2002)
Metadata have a long tradition in several areas. Metadata help to structure data or documents and to classify the contents. Today it is important to recognize the power of existing metadata (thesauri, classifications, ...) and to use such metadata and to expand such metadata for advanced data acquisition and information retrieval. To expand metadata modern learning sys tems should be used and an open communication model, that integrates different aspects of data and metadata. Results of an information retrieval project are described and a new multilevel model of metadata is introduced.